Exploring the Foundation of Genomics: A Northern Blot Reference set for the Comparative Analysis of Transcript Profiling Technologies. Issue 8 (2004) - Kemmer, Danielle; Faxén, Margareta; Hodges, Emily; Lim, Jonathan; Herzog, Elena; Ljungström, Elsebrit; Lundmark, Anders; Olsen, Mary K.; Podowski, Raf; Sonnhammer, Erik L. L.; Nilsson, Peter; Reimers, Mark; et al.
Abstract : In this paper we aim to create a reference data collection of Northern blot results and demonstrate how such a collection can enable a quantitative comparison of modern expression profiling techniques, a central component of functional genomics studies. Historically, Northern blots were the de facto standard for determining RNA transcript levels. However, driven by the demand for analysis of large sets of genes in parallel, high-throughput methods, such as microarrays, dominate modern profiling efforts. To facilitate assessment of these methods, in comparison to Northern blots, we created a database of published Northern results obtained with a standardized commercial multiple tissue blot (dbMTN). In order to demonstrate the utility of the dbMTN collection for technology comparison, we also generated expression profiles for genes across a set of human tissues, using multiple profiling techniques. No method produced profiles that were strongly correlated with the Northern blot data. The highest correlations to the Northern blot data were determined with microarrays for the subset of genes observed to be specifically expressed in a single tissue in the Northern analyses. The database and expression profiling data are available via the project website (http://www.cisreg.ca). We believe that emphasis on multitechnique validation of expression profiles is justified, as the correlation results between platforms are not encouraging on the whole. Supplementary material for this article can be found at: http://www.interscience.wiley.com/jpages/1531-6912/suppmat